Alinhamento estratégico das competências de marketing : um estudo nas indústrias do polo moveleiro de Arapongas-PR - Corneta, Alexandre Luiz (2008)
This work is proposed to meet the current development of marketing competences in researched organizations and analyze their adjustment depending on competitive strategy adopted and synthesized in the proposed value to the customer. For this, methodologically ran up a descriptive quantitative survey study with the companies that makes the cluster of furniture industry in the city of Arapongas/ PR, where those responsible for marketing functions of the organizations were interviewed. Overall, the results indicate the existence of raised a group of companies with some kind of alignment between the marketing competences and external strategy, even with minimum levels of those competences development considered as essential, given the parameters of the study. As a contribution the work presents a method for the management and the understanding of the relationship between the strategic planning and marketing functions of the organization, here condensed in the matrix of study used for research and categorization of strategic alignment.